Pemberdayaan remaja melalui edukasi gizi sebagai upaya pencegahan stunting sejak dini - Hasriani, St. Hasriani; Pratiwi, Wilda Rezki; Qardhawijayanti, Suci; Murtini, Murtini (JOURNAL of Public Health Concerns, 2025)
Background: Indonesia has one of the highest stunting rates in the world, with nearly 25% of Indonesian children under five affected by stunting. The Nutritional Status Research (SSGI) from the Indonesian Ministry of Health revealed that in 2021, stunting affected 24.4% of children under five across the country. Providing adequate nutrition during adolescence and educating women about stunting is a strategy to prevent anemia and contribute to preventing future stunting. Purpose: To increase knowledge about nutrition and stunting among adolescents as an effort to prevent stunting from an early age. Method: This activity was held on September 16, 2025, in Amparita Village, Sidenreng Rappang Regency, with the theme "Preventing Stunting Through Early Nutrition Education." The activity was attended by village officials and local health cadres, and involved 24 adolescent respondents from the Amparita Village community. The outreach included educational material presented through leaflets, covering nutritional issues in adolescents, knowledge of the First 1,000 Days of Life, balanced nutrition, stunting prevention, and understanding healthy eating. Participants' knowledge gains and changes were evaluated by comparing pre-test and post-test data. Results: Data obtained showed that the majority of respondents' knowledge before (pre-test) the educational activity was in the poor category 20 respondents (83.3%), while the majority of respondents' knowledge after the education was in the good category 22 respondents (91.7%). Conclusion: The community service activity, which provided education on nutritional issues for adolescents, went well. The education provided was very effective in increasing adolescents' knowledge of nutritional issues and made a positive contribution as a strategic step in preventing stunting early in the community. Suggestion: It is hoped that health education activities can be implemented regularly both in schools and in adolescent communities. It is also hoped that in addition to educational activities, nutritional behavior mentoring and nutritional consultation interventions will be provided so that the knowledge gained can be effectively applied. Keywords: Adolescents; Health education; Nutrition; Stunting Pendahuluan: Angka stunting di Indonesia termasuk yang tertinggi di dunia, dimana dengan hampir 25% anak balita di Indonesia terdampak stunting. Riset Status Gizi (SSGI) dari Kementerian Kesehatan Republik Indonesia mengungkapkan bahwa pada tahun 2021, stunting memengaruhi 24.4% balita di seluruh Indonesia. Sebagai upaya dengan memberikan pemenuhan gizi pada masa remaja dan mengedukasi perempuan tentang stunting merupakan strategi untuk mencegah terjadi anemia dan berkontribusi dalam pencegahan terjadinya stunting di masa datang. Tujuan: Untuk meningkatkan pengetahuan tentang gizi dan stunting pada remaja sebagai upaya pencegahan stunting sejak dini. Metode: Kegiatan ini dilaksanakan pada tanggal 16 September 2025 di Desa Amparita Kabupaten Sidenreng Rappang dengan tema “Cegah Stunting Melalui Edukasi Gizi Sejak Dini”. Kegiatan dihadiri perangkat desa, kader kesehatan setempat dan melibatkan 24 remaja sebagai responden yang merupakan bagian dari masyarakat Desa Amparita Kabupaten Sidenreng Rappang. Penyuluhan berupa edukasi berupa pemaparan materi dengan media leaflet, yang meliputi masalah gizi pada remaja, pengetahuan tentang 1000 Hari Pertama Kehidupan, asupan gizi seimbang, pencegahan stunting, dan pengertian menu makanan sehat. Peningkatan dan perubahan pengetahuan peserta, di evaluasi dengan membandingkan ata sebelum kegiatan (pre-test) dengan data sesudah kegiatan (post-test). Hasil: Mendapatkan data bahwa sebagian besar tingkat pengetahuan responden sebelum (pre-test) kegiatan edukasi dalam kategori kurang yaitu sebanyak 20 orang (83.3%), sedangkan tingkat pengetahuan responden setelah edukasi menjadi mayoritas dalam kategori baik yaitu sebanyak 22 orang (91.7%). Simpulan: Kegiatan pengabdian kepada masyarakat yang dilaksanakan dengan memberikan edukasi tentang masalah gizi pada remaja telah berjalan dengan baik. Edukasi yang diberikan sangat efektif dalam meningkatkan pengetahuan remaja tentang masalah gizi pada remaja dan memberikan kontribusi positif menjadi langkah strategis dalam pencegahan terjadinya stunting sejak dini pada masyarakat. Saran: Diharapkan kegiatan edukasi kesehatan dapat dilaksanakan secara berkala baik disekolah maupun dikomunitas remaja. Diharapkan juga selain kegiatan edukasi untuk dilakukan pendampingan perilaku gizi dan intervensi konsultasi gizi agar pengetahuan yang diperoleh dapat diterapkan dengan baik.